دور الحكامة في تحسین جودة وأداء مؤسسات التعلیم العالي د ا رسة مقارنة لنتائج التقییم الذاتي لمیدان الحكامة بین المركز الجامعي مرسلي عبد الله - تیبازة – - bedoui, samia (Finance and Business Economies Review, 2018)
Academic governance is one of the most important modern strategies adopted by international universities and has achieved positive results in improving its performance and guaranteeing its quality. The importance of the current study is to highlight the national reference to quality assurance adopted in Algerian higher education, and to highlight the role and effectiveness of the self-evaluation process in the field of governance in improving the quality and performance of institutions of higher education by analyzing and comparing the results of the self-evaluation of two university centers for 2017.